2004
DOI: 10.1128/mcb.24.17.7538-7547.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Cyclin-Dependent Kinase 4 Inhibits c-myc Tumorigenic Activities in Epithelial Tissues

Abstract: The proto-oncogene c-myc encodes a transcription factor that is implicated in the regulation of cellular proliferation, differentiation, and apoptosis and that has also been found to be deregulated in several forms of human and experimental tumors. We have shown that forced expression of c-myc in epithelial tissues of transgenic mice (K5-Myc) resulted in keratinocyte hyperproliferation and the development of spontaneous tumors in the skin and oral cavity. Although a number of genes involved in cancer developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 69 publications
(104 reference statements)
2
76
0
Order By: Relevance
“…Cdk4 provides a direct link between c-myc and cell-cycle regulation (Hermeking et al, 2000) and lack of Cdk4 inhibits c-myc's tumorgenic activities in epithelial tissues (Ortega et al, 2002). p21 and p27 inhibit Cdk2 kinase activity regardless of whether Cdk2 binds cyclin E or cyclin A. p21 and p27 are also capable of binding to cyclin D-Cdk4/6 complexes (Miliani de Marval et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cdk4 provides a direct link between c-myc and cell-cycle regulation (Hermeking et al, 2000) and lack of Cdk4 inhibits c-myc's tumorgenic activities in epithelial tissues (Ortega et al, 2002). p21 and p27 inhibit Cdk2 kinase activity regardless of whether Cdk2 binds cyclin E or cyclin A. p21 and p27 are also capable of binding to cyclin D-Cdk4/6 complexes (Miliani de Marval et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we already know that animals lacking Cdk4 are completely refractory to Ras-mediated skin carcinogenesis in vivo, whereas Cdk4 deficiency has no effect on the normal proliferation of keratinocytes in vitro (Rodriguez-Puebla et al 2002). Inactivation of Cdk4 also completely protects transgenic mice expressing cMyc under the control of the keratin-5 promoter from developing epithelial tumors (Miliani de Marval et al 2004). Similarly, cyclin D1 inactivation confers resistance to breast cancers induced by oncogenic Neu or Ras transgenes targeted to the mammary gland and to intestinal tumors resulting from Apc loss and constitutive ␤-catenin signaling (Hulit et al 2004).…”
Section: Implications For Cancermentioning
confidence: 99%
“…4 The analysis of gene-targeted mouse models indicated that Cdk2, Cdk4 and Cdk6 are only essential for the proliferation of some specialized cells, suggesting that Cdk inhibitors are likely to produce certain toxicities by affecting specific cells. 3,[5][6][7] Nonetheless, Cdk4 inhibition may be effective to prevent Myc-induced skin tumors, 8 Rasinduced breast cancer 9 or K-Ras-induced non-small-cell lung carcinoma. 10 These results suggest that Cdk inhibition may be exploited in clinical settings taking into consideration the cellular context of the tumor and the pathogenic spectrum of their mutations.…”
Section: Cell Cycle Entrymentioning
confidence: 99%